Study of neck shaft angle of femur in population of Bihar - Sinha, Rajiv Ranjan; Kumar, Binod; Kumar, Sanjay; Ratnesh, Ruchi; Akhtar, Md. Jawed; Fatima, Nafees (International Journal of Research in Medical Sciences, 2017)
Background: Neck shaft angle is the angle formed between the long axis of shaft and long axis of neck. Neck shaft angle of femur is an important parameter considering the biomechanics of hip joint. Neck shaft angle gives important information regarding race to which they belong. Normal neck shaft angle is in the range of 1200 -1400. Objective of the study was to find out the neck shaft angle of femur and correlate with the previous study. Methods: present study was conducted on 60 dry femur collected from different medical colleges of Bihar. The neck shaft angle was measured by Goniometer. Results: In this study the neck shaft angle of femur was 130.820, in male neck shaft angle of femur was 130.280 and in females it was 131.420. Conclusions: There is no significance difference between the male and female neck shaft angle. Orthopaedists use the normal range and mean of the neck shaft angle in diagnosis and treatment of the disease of hip. The angle is increased in poliomyelitis, congenital subluxation and dislocation of hip and decreased in congenital coxa vara.